Gadamer/Wittgenstein: Encuentros y desencuentros entre hermenéutica y filosofía del lenguaje ordinario - Balbontin, Cristóbal (2021)
There is a certain status quaestionis among philosophers that usually portrays analytic philosophy and hermeneutical phenomenology as conflicting. However, some decades ago, some neo-pragmatic interpretations of Wittgenstein have opened the possibility for an encounter with Gadamer’s hermeneutics. It is well known that Gadamer read Wittgenstein after the publishing of Truth and Method in 1960, and he found ideas that were familiar to him. We can see these agreements, for example, when Gadamer refers to what is hermeneutic in a proper sense, this is, to practice a critique of language to address metaphysical questions regarding the linguistic constitution of our being in the world. Thus, when Gadamer understands hermeneutics as interpretation, and relates it to the practical behavior of human beings in the world, which shares with Wittgenstein the idea that the meaning of language is marked by its social uses. Therefore, our goal is to present a reflection on the agreements and distances between both thinkers.